A study on the Development Model of Ctrip - Shang, Xian-Fa; Choi, Myeong-Cheol; Kan, Zhuo-Cuo (International Journal of Psychosocial Rehabilitation, 2020)
Ctrip, China's leading online tourism platform, has developed various forms of tourism products such as airline tickets, hotels, vacations, and business trips. To retain its competitive position, Ctrip must continuously develop a diversified offering to appeal to the ever-changing consumer demands. Companies must regularly update their offerings to participate in the online travel industry as travel experience searches and public comments on user review sites are continually changing. All online travel companies must face the challenge of playing to their advantages in the fierce market competition. Utilizing Ctrip as the research subject, this paper summarizes the enterprise competitiveness of Ctrip by using Porter’s five forces model analysis. This paper hopes to help online tourism enterprises in the increasingly fierce market competition, and promote the competitiveness of enterprises at the strategic level.